The Influence of Internal and External Quality Audit on The Sustainability of Surabaya Merchant Marine Polytechnic - Ibnu Fajarudin; Merdita Guesti (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: The era of globalization and free markets forces universities to organize themselves by introducing internal quality assurance to guarantee the quality of education and services. In addition to internal quality assurance, universities as labor producers also require quality assurance from certification bodies outside the university. Several previous studies examined the influence of internal and external quality audits on work productivity and employee performance. In this study, the effect was seen to be different from before, namely knowing the effect of internal and external quality audits on the sustainability of the Surabaya Merchant Marine Polytechnic. The purpose of this study was to determine whether internal and external quality audits affect the sustainability of the Surabaya Merchant Marine Polytechnic. Design/methodology/approach: This study uses quantitative research with a population and the sample is a work unit at the Surabaya Merchant Marine Polytechnic which is involved with internal and external quality audits. The data collection method in this study was to use questionnaires using multiple linear regression analysis. Tests in this study used SPSS statistics version 26. Findings: The conclusion of this study is that there is a significant influence between internal and external quality audits on the sustainability of the Surabaya Merchant Marine Polytechnic either partially or simultaneously. The variable that has the dominant influence on this study is the internal quality audit. Paper type: Research Paper.